Insight into microstructural architectures contributing to the tensile strength of continuous W-core SiC ﬁber. Issue 15 (December 2020) - Zhang, Y.; Wen, M.; Sun, G.X.; Huang, H.; Zhang, S.M.; Wang, M.J.; Zhang, K.; Pang, H.P.; Zheng, W.T.
Abstract: The properties of CVD silicon carbide (SiC) ﬁber are closely correlated with its complex microstructure; however, the microstructural architectures contributing to its strength are not well understood. Here, two kinds of W-core SiC ﬁbers (SiC-3200 and SiC-3800) coated with same C coating, possessing different tensile strength and discrepant microstructure in SiC portion, were fabricated by controlling deposition temperature during CVD process. The structure discrepancy contributing to the different tensile strength for both SiC fibers were explored by the combined Raman spectra, EPMA, SEM and HRTEM. It is revealed the high-crystallinity β-SiC columnar grains in the inner zone always evolve into a higher disorder character yet involving partial surviving columnar grains toward surface for both SiC fibers. However, as compared with SiC-3800 fiber, the slightly higher C over-stoichiometric composition yields lower-crystallinity SiC columnar grains across the radius for SiC-3200 fiber, further resulting in lower strength via forming smoother stepped fracture morphology.